Congenital Insensibility to Pain - Carlos Gustavo López Barrionuevo; Génesis Camila Romero Paredes; Byron Omar Montero Carpio (Medisur)
Congenital insensitivity to pain is a condition that is present at birth, the affected individual is unable to perceive physical pain. The main symptoms include: wounds, bruises, fractures, self-mutilations, which can go unnoticed due to lack of awareness of pain and cause damage to the patient's health that affects their quality of life. This research was carried out with the objective of identifying the most frequent type of congenital insensitivity to pain and its symptoms. The bibliographic search was carried out in the databases: Medline, Scielo, Elsevier, Google Scholar, Redalyc, Science Direct in the period from 2018 to 2022. A total of 20 articles were found, of which 14 were selected. The most frequent gene that affects this pathology is NTRK 1, consanguinity between parents is a risk factor for developing congenital insensitivity to pain. It presents a very varied clinical picture depending on the affected gene, doctors must carry out a thorough physical examination, especially a neurological one, to make a correct diagnosis.